(untitled) (Olhar de Professor, 2023)
This article problematizes the normative forecast of documents related to inclusion and praxis in the Freirean perspective, trying to discuss the similarities and differences between the normative documents of inclusion and the practices of school learning according to Freirean theory. To this end, a bibliographic review was adopted as a methodological procedure. From the evaluation, two axes emerge: approximations between normative documents of inclusion and learning practices according to Freirean theory; distance between normative documents of inclusion and learning practices according to Freirean theory. The first axis is more present in the documents and is divided into two groups: Protagonism and Participation, two Freirean assumptions. The second axis appears more subtly and is associated with the banking education fought by Freire. It can be considered that the level of approximation between the normative documents of inclusion and Freire’s theory does not reverberate in the concrete educational praxis of schools, which refers to the training fragility of professionals. It is considered useful to revisit the initial and continuing education of professionals in education for inclusion, as well as rigorously applying what is foreseen in the normative documents and taking into account the knowledge of all people involved in the inclusion process in the formulation of public policies of inclusion.